The new Webster's dictionary of the English language (New York : Lexicon International/Publishers Guild Group, 1995)
The present book aims to combine the best features of the general dictionary and the short-entry encyclopaedia, and hence to be of maximum usefulness to those who seek word-facts and fact-facts. The format was simplified by using a single alphabetical listing rather than separate ones for biographies, gazetteer, historical events, and so forth.
ne 05/10/2021
Loans
Keywords: English language